The intricate interplay between ferroptosis and efferocytosis in cancer: unraveling novel insights and therapeutic opportunities - Firouzjaei, Ali Ahmadizad; Mohammadi-Yeganeh, Samira (Frontiers in Oncology, 2024)
The complex interplay between ferroptosis and efferocytosis in cancer has attracted significant interest recently. Efferocytosis, the process of eliminating apoptotic cells, is essential for preserving tissue homeostasis and reducing inflammation. However, dysregulation of efferocytosis can have profound effects on cancer. Apoptotic cells accumulate because of impaired efferocytosis, which triggers chronic inflammation and the release of pro-inflammatory chemicals. Surprisingly, accumulating evidence suggests that dysregulation of ferroptosis- a form of controlled cell death characterized by lipid peroxidation and the buildup iron-dependent reactive oxygen species (ROS)-can influence efferocytic activities within the tumor microenvironment. Dysfunctional iron metabolism and increased lipid peroxidation, are associated with ferroptosis, resulting in inadequate apoptotic cell clearance. Conversely, apoptotic cells can activate ferroptotic pathways, increasing oxidative stress and inducing cell death in cancer cells. This reciprocal interaction emphasizes the complex relationship between efferocytosis and ferroptosis in cancer biology. Understanding and managing the delicate balance between cell clearance and cell death pathways holds significant therapeutic potential in cancer treatment. Targeting the efferocytosis and ferroptosis pathways may offer new opportunities for improving tumor clearance, reducing inflammation, and sensitizing cancer cells to therapeutic interventions. Further research into the interaction between efferocytosis and ferroptosis in cancer will provide valuable insights for the development of novel therapies aimed at restoring tissue homeostasis and improving patient outcomes.